Personality testing and workplace training: Exploring stakeholders, products and purpose in Western Europe. Issue 3 (3rd April 2017) - Lundgren, Henriette; Kroon, Brigitte; Poell, Rob F.
Abstract : Purpose: The purpose of this paper is to explore how and why personality tests are used in workplace training. This research paper is guided by three research questions that inquire about the role of external and internal stakeholders, the value of psychometric and practical considerations in test selection, and the purpose of personality test use in workplace training. Design/methodology/approach: This research paper uses multiple-case study analysis. Interviews, test reports, product flyers and email correspondence were collected and analyzed from publishers, associations, psychologists and human resource development (HRD) practitioners in Germany, the UK and The Netherlands between 2012 and 2016. Findings: Themes emerge around industry tensions among practitioners and professional associations, psychologists and non-psychologists. Ease of use is a more important factor than psychometrics in the decision-making process. Also, practitioners welcome publishers that offer free coaching support. In the process of using tests for development rather than assessment, re-labeling takes place when practitioners and publishers use positive terms for personality tests as tools for personal stocktaking and development. Research limitations/implications: Despite extensive data collection and analysis efforts, this study is limited by its focus on a relatively small number of country cases and stakeholders per case. Practical implications: By combining scientific evidence with practical application, stakeholders can take first steps toward more evidence-based HRD practice around personality testing in workplace training. Originality/value: Little academic literature exists on the use of personality testing in workplace training. Without a clear understanding of the use of personality testing outside personnel selection, the current practice of personality tests for developmental purposes could raise ethical concerns about the rights and responsibilities of test takers.